Theoretical model of autoimmune thyreoitic II. Pathogenesis and two-autoantigen model of the disease - Gladkikh, D. P.; Gordiyenko, E. A. (Biophysical Bulletin, 2006)
The theoretical model of autoimmune thyroiditis (AIT) to describe the disease running is formulated on the basis of the equations of immunocompetence cells, macrophages, antigens, and antibodies balance. The following suppositions are at the base of the model of AIT. The original cause of AIT is the particular destruction of thyroid gland follicles under influence of a cytotoxic agent. As a result, thyroglobulin molecules from ruined follicles release into interfollicular liquid and begin to circulate in lymphatic and blood vessels. As normally thyroglobulin is physiologically isolated from the immune system, the released from ruined follicles thyroglobulin molecules are distinguished as strange substances or autoantigens causing the correspondent immune reaction. Have being bound to the external surface of the epithelial layer of unruined follicles thyroglobulin forced the immune system to distinguish thymocytes with joined thyroglobulin molecules as corpuscular antigens which should be destroyed and removed from the organism. The  destruction of thyroglobulin - marked thyrocytes itself leads to release of new portions of thyroglobulin into the system of circulation. After all, this process may cause particular or complete destruction of thyroid gland parenchyma and decrease or full loss of its hormone formation function.